Morphology‐Driven Sensitivity Enhancement of MEH‐PPV Langmuir‐Blodgett Films on Plastic Substrates for NO2 Gas. Issue 1 (3rd January 2018) - Saxena, Vibha; Chandran, Sridevi; Choudhury, Sipra; Singh, Ajay; Ganapathi, Kailasa; Kaur, Manmeet; Tanvi,; Muthe, Kunal P.; Gadkari, Sanjay C.
Abstract: 3D ordered Langmuir–Blodgett (LB) films of poly[2‐methoxy‐5‐ (2‐ethylhexyloxy)‐1,  4‐phenylenevinylene] (MEH‐PPV) were prepared via thermal annealing. Surface properties of MEH‐PPV prepared by using different solvents, through both LB and Spin Casting techniques, were examined at the air‐water interface by measuring surface pressure‐area isotherms and Brewster Angle Microscopy. Dramatically different surface morphologies were obtained for spin cast and LB films, both prepared by using different solvents. The annealed LB films showed enhanced NO2 gas sensing as compared to spin cast films. Spectroscopy and morphological analyses reveal that enhanced response of LB films toward NO2 gas is due to their 3D ordered morphology, preferred molecular orientation for in‐plane transport as well as higher surface area. Abstract : 3D ordered MEH‐PPV LB films show enhancedNO2 gas sensing vis‐à‐vis spin cast films